THE EFFECT OF AMMONIUM-BASED NPK FERTILIZERS ON THE GROWTH OF MANGROVE SEEDLINGS Rhizopora mucronata AND Rhizopora stylosa - Hanindipto, Fasa Aditya; Rasima Daulay, Fathin; Puji Rahayu, Sarwendah; Putri Irsani, Izma; Rizki Rachmani, Alfina; Evangelina, Helga (BRIN - Badan Riset dan Inovasi Nasional, 2025)
Mangroves play an important role in coastal ecosystems, but their growth is often limited by nutrient availability, particularly nitrogen, phosphorus, and potassium (NPK) availability. The use of ammonium-based fertilizers can provide additional benefits by accelerating the growth of mangrove seedlings. This study examines the influence of various doses of ammonium-based NPK fertilizers on the growth of two mangrove species, Rhizophora mucronata and Rhizophora stylosa, The study was carried out in two different places with distinct environmental characteristics, Rhizophora mucronata was planted near land, whereas Rhizophora stylosa was planted in open areas near the sea. The seedlings received dosages of ammonium-based NPK fertilizer. Periodic measurements of growth characteristics, including leaf length, root length, plant height, and SPAD (Soil Plant Analysis Development) index, were conducted and tested statistically. Rhizophora mucronata responded effectively to ammonium-based fertilizer treatment, increasing plant height, root length, and chlorophyll content at an optimal dose of 0.9 grams per, although shoot growth decreased. These data show that Rhizophora mucronata is more responsive to ammonium- based fertilizer treatments than is Rhizophora stylosa under the evaluated environmental conditions, although the fertilizer dosage had no significant effect.